Frontispiece: Pnictogen‐Functionalised C1 Ligands: MC‐ARn (n=0, 1, 2, 3). Issue 17 (22nd March 2021) - Colebatch, Annie L.; Frogley, Benjamin J.; Hill, Anthony F.; Onn, Chee S.
Abstract : Phosphorus, etymologically "the bringer of light, " and the other heavy pnictogens are represented by lit matches (loosely) coloured by their respective flame tests. Read more about recent developments in the chemistry of pnictogen‐functionalised C1 ligands, L n MCAR m (A=P, As, Sb, Bi; m =0, 1, 2, 3) in the Review by A. Hill et al. on page 5322 .